The Role Of Financial Management In Improving Corporate Sustainability: A Case Study Of A State-Owned Company - Karona Cahya Susena (Journal of Research in Social Science and Humanities, 2025)
A company needs to improve sustainability in order to prosper its owners and shareholders and this can be done by implementing financial management policies. This development research aims to review whether the company's value can be affected by the financial management policies of each state-owned company listed on the IDX in 2019-2021. Almost all companies feel the impact of the Covid-19 pandemic, many state-owned companies distribute large dividends and also provide funding or invest in startup companies. In addition, the number of investors during the Covid-19 pandemic has also increased rapidly. The type of research used in this study is explanatory using a quantitative approach. The subjects of this study are state-owned companies listed on the IDX in 2019 to 2021. The purposive sampling technique was used for the sample collection process and 16 companies were obtained with 48 observations that met the sample selection criteria. Furthermore, the analysis applied was multiple linear regression analysis. Testing is needed when you want to know the relationship between variables, so a test is carried out using the classical assumption test. The results of all the analyses carried out prove that there is no influence of policies or can also be called funding decisions and investment policies on the value of a company, especially for BUMN. However, it is different with dividend policies which have been proven to have a positive impact on the value of the company.